PROFIL INDEKS MASSA TUBUH ATLET KONI PROVINSI RIAU TAHUN 2023 - P. Simarmata, Saut Martua; Sulastio, Agus; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
bstract: Anthropometric measurement is performed on the KONI tlet Prov.Riau to find out the ideal of the mass index of the bodies that the athlete has. Thepurpose of this research is to find out the body composition of the Riau Province. Thepopulation and samples in this study were using a total sampling technique of 327athletes. The instrument in this study uses anthropometric instruments (BB/TB) that canbe used to determine IMT, Based on the results of the research and the purpose of thisstudy, then it can be concluded that the measurement category of the body mass index of the average athlete KONI Riau belongs to the ideal weight category, or normal weight.Or of the 77 athletes, 63.64% had an ideal IMT.Key Words: Index Body Mass, Athlete